A life-table model estimation of the parr capacity of a late 19th century Puget Sound steelhead population - Nick Gayeski; George Pess; Tim Beechie (Canadian Science Publishing, 2016)
An age-structured life-cycle model of steelhead (Oncorhynchus mykiss) for the Stillaguamish River in Puget Sound, Washington, USA, was employed to estimate the number of age-1 steelhead parr that could have produced the estimated adult return of 69 000 in 1895. We then divided the estimated parr numbers by the estimated area of steelhead rearing habitat in the Stillaguamish River basin in 1895 and under current conditions to estimate density of rearing steelhead then and now. Scaled to estimates of total wetted area of tributary and mainstem shallow shoreline habitat, our historic estimates averaged 0.39-0.49 parr·m−2, and ranged from 0.24 to 0.7 parr·m−2. These values are significantly greater than current densities in the Stillaguamish (mainstem average: 0.15 parr·m−2, tributaries: 0.07 parr·m−2), but well within the range of recent estimates of steelhead parr rearing densities in high-quality habitats. Our results indicate that modest improvement in the capacity of mainstem and tributary rearing habitat in Puget Sound rivers will yield large recovery benefits if realized in a large proportion of the area of river basins currently accessible to steelhead.